PROFILE OF PULMONARY AND EXTRA PULMONARY TUBERCULOSIS USE GENEXPER AT THE PIRNGADI HOSPITAL MEDAN - Eva Sartika Daposang; Fenny Hasanah; Dewi Silaban (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2021)
Mycobacterium tuberculosis as the bacteria that causes TB disease where the healing process takes a long time, using boredom and drug blockages in TB sufferers. This is one reason germs become resistant to several types of anti-tuberculosis drugs known as TB Multi Drug Resistance (MDR TB). The molecular rapid test (TCM) method using GenExper can quickly determine ATD resistance. This study aims to see the results of TCM examination using GenExper in patients with pulmonary tuberculosis and extra pulmonary tuberculosis at dr. Pirngadi Medan. This study used a cross-sectional method by taking laboratory data from the GenExper examination contained in the medical records of patients diagnosed with tuberculosis at Pirngadi Hospital, Medan. Samples obtained from patients using GenExper from January to December 2018 obtained 354 patients with 68.1% more TB incidence in male patients (241/354) than women by 31.9% (113/354). The patients most affected by TB were elderly people aged 56-65 years with a proportion of 23.7%. The largest population affected by TB is self-employed 30.5% and the highest level of education diagnosed is high school graduates 60.5%. Most patients suffered from pulmonary TB at 86.4%.